The use of modern remote communication tools in improving processes of a non-profit organization based on the example of the student government of the Wroclaw University of Economics and Business - Chomiak-Orsa, Iwona; Kłus, Radosław (Wykorzystanie nowoczesnych narzędzi komunikacji zdalnej w doskonaleniu procesów organizacji non-profit na przykładzie samorządu studentów Uniwersytetu Ekonomicznego we Wrocławiu, 2021)
The use of remote communication tools is nowadays becoming a phenomenon which is more and more visible not only in companies, but also in other entities of the economy. The use of modern remote communication tools allows for increasing the functional efficiency of the entity and improving contact between members of the unit. The paper presents the actual ways in which modern remote communication tools are used both between the members of a student organisation and with other entities, the types of these tools and the characteristic nature of such an entity in the era of the coronavirus pandemic.
Informatyka Ekonomiczna = Business Informatics, 2021, Nr 3 (61), s. 1-14
Keywords: non-profit organizations; remote communication; student organization; stakeholders; process improvement; komunikacja zdalna; organizacja studencka; interesariusze; doskonalenie procesów; działalność non-profit